Profile of nursing and medicine students of Universidade Federal do Rio Grande regarding suicidal ideation (Research, Society and Development, 2021)
Objectives: Quantify a total of students with ideation suicidal among nursing and medicine graduates of the Universidade Federal do Rio Grande (FURG) and characterize the profile who present this disorder. Methods: Descriptive, quantitative, and cross-sectional study. Were applied electronic questionnaires, from March to June 2019, to nursing and medicine students of FURG. Results: From a total of 223 completed questionnaires, 45 showed characteristics of suicidal ideation. Predominance of nursing students (75.56%, n=34), women (84.44%, n=38), single people (42.22%, n=19), and mean age of 24.6 (±7.61) years old. Suicidal ideation was more presented in 3rd semester of nursing and 1st year of medicine. Conclusion: Suicidal ideation, be it passive or active, induce the necessity of carer sight about those who suffer. Discussing the theme motivates solutions and, consequently, treatments to be applied, in order to, those who will serve the population could exercise their work in its technical and emotional fullness.